2011
DOI: 10.1093/jjco/hyr131
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Gemcitabine and Paclitaxel is a Favorable Option for Patients with Advanced or Metastatic Urothelial Carcinoma Previously Treated with Cisplatin-based Chemotherapy

Abstract: Objective: To evaluate the efficacy and toxicity of a gemcitabine and paclitaxel regimen for patients with advanced urothelial carcinoma who had previously been treated with methotrexate, vinblastine, doxorubicin and cisplatin chemotherapy, and to determine the prognostic factors for survival in second-line chemotherapy. Patients were evaluated every two cycles by imaging study. Results: Ten of 24 patients (42%) had major response to the gemcitabine and paclitaxel regimen, including 2 patients (8%) who had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
3
8
2
Order By: Relevance
“…Our results are in line with recent reports demonstrating that in patients treated with a second-line combination regimen including GP regimen for mUC, the ORR was 8.6%–41.7% and median OS was 4.8–12.4 months. 8 , 19 , 21 , 27 31 Compared with these results, the oncological outcomes of our study in elderly patients were encouraging with regard to a durable response rate and survival, therefore, supporting the use of second-line GD therapy in elderly patients with a comorbidity.…”
Section: Discussionsupporting
confidence: 64%
“…Our results are in line with recent reports demonstrating that in patients treated with a second-line combination regimen including GP regimen for mUC, the ORR was 8.6%–41.7% and median OS was 4.8–12.4 months. 8 , 19 , 21 , 27 31 Compared with these results, the oncological outcomes of our study in elderly patients were encouraging with regard to a durable response rate and survival, therefore, supporting the use of second-line GD therapy in elderly patients with a comorbidity.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies have examined the various prognostic factors of patients. Buti et al identified nine studies (29)(30)(31)(32)(33)(34)(35)(36)(37)) that aimed at evaluate the prognostic factors of 1,273 patients in a second-line treatment setting. In most studies, PS, Hb, and visceral metastasis were identified as the main independent prognostic factors for OS (38).…”
Section: Discussionmentioning
confidence: 99%
“…Various GEM and PTX regimens have been described in previous reports. The most representative and common regimen is administration of GEM on day 1, 8, and 15 and PTX on day 1 [11, 15, 17, 18]. In another report, the day 15 GEM dose was omitted in 31 % of courses, almost always due to myelosuppression [11].…”
Section: Discussionmentioning
confidence: 99%